TINJAUAN YURIDIS TERHADAP PEMENUHAN HAK BAGI TENAGA KERJA DISABILITAS MENURUT HUKUM POSITIF DI INDONESIA - Sigalo Dharma Putra; H. Zaeni Asyhadie (Private Law, 2021)
Most people with disabilities do not have a decent life because they do not have the opportunity to work. This fact contradicts the provisions of Law Number 8 of 2016 concerning Persons with Disabilities, which states that persons with disabilities are entitled to equal opportunities and treatment to work in accordance with Janis and their level of disability, education and abilities. The problem is, the provisions regarding workers with disabilities are not regulated in the main Manpower Act, namely Law Number 13 of 2003 concerning Manpower. The type of research used is normative legal research using a statute approach and a conceptual approach. And it can be concluded that there has been an inconsistency between laws and regulations and a legal vacuum regarding the right to work for workers with disabilities in the Manpower Act.